2017
DOI: 10.1039/c7cc05818g
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of RZn(N,O)-type complexes as an efficient route to zinc alkoxides not accessible via the classical alcoholysis path

Abstract: nation of zinc alkyls, 6-8 herein we describe the synthesis and Scheme 1 Representation of divergent solid-state product formation by the controlled oxygenation of alkylzinc complexes incorporating monoanionic X,Y-bidentate ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…Moreover, we have also emphasized the essential role of the coordination state of the oxygenated organoaluminum and organozinc compounds, as well as the geometric requirements of an O 2 molecule approaching the metal centre . Apart from the fundamental aspects, these systematic studies have advanced rational design of metal alkyl/air systems as radical initiators for organic reactions, stoichiometric and catalytic asymmetric epoxidation of enones and pave the way to well‐defined metal alkoxides (not accessible through the classical alcoholysis path) as potential initiators of cyclic esters polymerization as well as to a new approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/air systems …”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, we have also emphasized the essential role of the coordination state of the oxygenated organoaluminum and organozinc compounds, as well as the geometric requirements of an O 2 molecule approaching the metal centre . Apart from the fundamental aspects, these systematic studies have advanced rational design of metal alkyl/air systems as radical initiators for organic reactions, stoichiometric and catalytic asymmetric epoxidation of enones and pave the way to well‐defined metal alkoxides (not accessible through the classical alcoholysis path) as potential initiators of cyclic esters polymerization as well as to a new approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/air systems …”
Section: Introductionmentioning
confidence: 96%
“…Moreover, despite the structural diversity of isolated metal alkylperoxides with non‐redox‐active centres, knowledge of their modes of further transformation still appears to be fragmentary. Our group's systematic studies on the reactivity of zinc alkyls towards O 2 have demonstrated that not only zinc alkylperoxides and alkoxides, but also zinc peroxide, hydroxide, oxo and even carboxylate species can be isolated from the controlled oxygenation of organozincs. Furthermore, we have provided compelling evidence that a variety of oxygenation products result from the decomposition of (L)ZnOOR species mediated by the O−O bond scission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, the multifaced chemistry of zinc alkoxides has a particularly long history and can be traced back to Frankland's pioneering studies [3] . This interest in zinc alkoxides has been driven by several perspectives including synthetic methodology, [4–9] molecular structure, [4–20] reactivity, [9–11, 16, 18, 20–29] potential applications of zinc alkoxides both in catalytic reactions, [21, 23, 24, 30, 31] and more recently in materials science as predesigned precursors of zinc oxide nanostructures [15, 22, 26–29, 32–34] . Over time, a wide variety of their structural motifs (see below) and diverse transformations in the solid state and solution emerged.…”
Section: Introductionmentioning
confidence: 99%